INCREASING THE ROLE OF BANK CREDIT IN ENSURING THE FINANCIAL STABILITY OF BUSINESS ENTITIES (International Congress on Economics, Management and Business Studies, 2026)
This article examines the role of bank credit in ensuring the financial stability of business entities. In modern economic conditions, access to financial resources is one of the key factors determining the sustainable development and competitiveness of enterprises. Bank loans enable businesses to finance investment projects, replenish working capital, modernize production facilities, introduce innovative technologies, and expand their operations. At the same time, effective use of credit resources requires appropriate financial planning and risk management. The article identifies the main ways to increase the role of bank lending in strengthening the financial stability of business entities, including improving lending mechanisms, reducing the cost of credit resources, developing long-term financing, introducing modern digital technologies, and improving cooperation between banks and enterprises.
Keywords: Bank credit, financial stability, business entities, lending, investment, working capital, financial resources, credit risk, entrepreneurship.